February/March moth flights in Manawatu have important implications for porina management - Ferguson, C.M.; Gee-Taylor, M.A.; Richards, N.K. (New Zealand Plant Protection, 2016)
Porina (Wiseana spp) a complex of seven species three with two haplotypes are intractable pests on many New Zealand farms Regional differences in species composition and timing of caterpillar development impact on porina control At Glencorran Station Manawatu porina moth flights were monitored using a light trap from 2012/13 to 2015/16 The most common species trapped was W copularis W signata was also regularly collected Both species flew from October to March but the main flight period occurred in late February/ early March and consisted almost entirely of northern haplotype W copularis The time of peak flight means the most cost effective control strategy application of diflubenzuron against young caterpillars should be undertaken in June several months later than traditionally considered for most porina prone areas Furthermore caterpillars from the late flights will attain large size in July/August which may coincide with low porina feeding deterrent and toxin production by the AR37 ryegrass endophyte Consequently when caterpillars are most voracious protection of ryegrass plants by the endophyte is at a low ebb and may help explain why some AR37 ryegrass pastures especially in colder areas are damaged by porina